A Drosophila model of the neurodegenerative disease SCA17 reveals a role of RBP-J/Su(H) in modulating the pathological outcome. - Ren, J.; Jegga, A.G.; Zhang, M.; Deng, J.; Liu, J.; Gordon, C.B.; Aronow, B.J.; Lu, L.J.; Zhang, B.; Ma, J. (Human Molecular Genetics, 2011)
Expanded polyglutamine (polyQ) tract in the human TATA-box-binding protein (hTBP) causes the neurodegenerative disease spinocerebellar ataxia 17 (SCA17). To investigate the pathological effects of polyQ expansion, we established a SCA17 model in Drosophila. Similar to SCA17 patients, transgenic flies expressing a mutant hTBP protein with an expanded polyQ tract (hTBP80Q) exhibit progressive neurodegeneration, late-onset locomotor impairment and shortened lifespan. Microarray analysis reveals that hTBP80Q causes widespread and time-dependent transcriptional dysregulation in Drosophila. In a candidate screen for genetic modifiers, we identified RBP-J/Su(H), a transcription factor that contains Q/N-rich domains and participates in Notch signaling. Knockdown of Su(H) by RNAi further enhances hTBP80Q-induced eye defects, whereas overexpression of Su(H) suppresses such defects. While the Su(H) transcript level is not significantly altered in hTBP80Q-expressing flies, genes that contain Su(H)-binding sites are among those that are dysregulated. We further show that hTBP80Q interacts more efficiently with Su(H) than wild-type hTBP, suggesting that a reduction in the fraction of Su(H) available for its normal cellular functions contributes to hTBP80Q-induced phenotypes. While the Notch signaling pathway has been implicated in several neurological disorders, our study suggests a possibility that the activity of its nuclear component RBP-J/Su(H) may modulate the pathological progression in SCA17 patients.